Analisis Kualitas Air Hygiene Sanitasi Secara Fisika dan Kimia di Perumahan Green View Sunggal - Devi Lestari; Imas Masriah; Sulwiyatul Kamariah Sani; Siti Mahmudha; Adelia Yesya Putri Hasibuan (Yayasan Literasi Sains Indonesia, 2025)
This study analyzed the quality of borehole water in Green View Sunggal Housing located in a rice field area. This research used a descriptive analytical method with a cross-sectional design. Samples were taken from 25 boreholes through a purposive sampling technique divided into three zones: north (8 wells), middle (7 wells), and south (10 wells). The parameters evaluated included physical aspects (temperature, odor, taste, color, turbidity) and chemical aspects (pH, hardness, Fe, Mn, nitrate, nitrite, chloride). Laboratory analysis was carried out at the Medan State Polytechnic following SNI standards and the APHA method, with statistical analysis using SPSS for Pearson correlation and linear regression. The results showed that the majority of parameters met the standards of Permenkes No. 32 of 2017. The parameters of temperature, odor, taste, hardness, manganese, nitrate, nitrite, and chloride reached a compliance level of 100%. However, there were discrepancies in color (92%), turbidity (84%), pH (64%), and iron content (80%). Samples from the southern zone adjacent to rice fields within a 200-meter radius showed significant problems with acidic pH (5.8-6.4) and excessive iron content (1.12-1.42 mg/L). Statistical analysis revealed significant correlations between well depth, distance from rice fields, and water quality. Distance from rice fields was the strongest predictor for nitrate (R² = 0.475) and iron (R² = 0.374). The study concluded that better environmental management is needed to maintain and improve water quality in the residential area.